Improving student attitudes: a study of a mathematics curriculum innovation - Curtis, Karena M. (Kansas State University, 2006)
The purpose of this study was to assess the impact of student attitudes in a college algebra mathematics classroom when lessons are primarily composed of standards-based pedagogy. National reports advocate for a change in teaching K-12. Nowhere is this more needed than in community colleges where students are taught in traditional formats and rarely challenged to make connections between mathematics and their personal experiences. A thorough review of the literature shows the need for mathematics reform at every level, including the college mathematics classroom. There are several national reports, Principles and Standards for School Mathematics, Adding it Up, How People Learn, and Undergraduate Programs and Courses in the Mathematical Sciences, that have been published to address the need to change mathematics teaching and learning. They are advocates for the implementation of standards-based instruction into the mathematics classroom. This study focused on students’ perceptions about the nature of mathematics and learning mathematics, specifically, does such a learning environment impact students’ perceptions of being a student of mathematics in the areas of confidence, anxiety, enjoyment, and motivation, and relevance of mathematics in personal and professional experiences. Over the course of one semester, two sections of college algebra students participated in the study. By using both qualitative and quantitative data collection methods, the study was able to see if there was an impact in student attitudes toward mathematics. The standards-based pedagogy used in this study was cooperative learning, problem solving, discourse, and the graphing calculator. Changes in attitude were determined by attitudinal surveys, student questionnaires, observations, and focus groups. College algebra students had a statistically significant change in their enjoyment of mathematics. Although the other attitudes, confidence, motivation, and value did not have a statistically significant change, the qualitative data indicates a change in these attitudes did occur. This study identified that cooperative learning, problem-solving, discourse, and graphing calculators increased student confidence in doing mathematics because they felt more competent in working problems on exams. Students also found the class enjoyable, anxiety was reduced as students became more familiar with the instructional strategies, and students recognized the value of mathematics for job skills and personal business.
Keywords: mathematics; standards-based; college-level; Education, Curriculum and Instruction (0727); Education, Higher (0745); Education, Mathematics (0280)